Die britischen Inseln über dem Winde (Kleine Antillen): Grundbesitz und Betriebsformen in ihrem Einfluß auf das Bild der Kulturlandschaft - Blume, Helmut (ERDKUNDE, 1961)
In this paper the British Islands within the arc of the Lesser Antilles, where agriculture determines the economic life, are investigated as regards size, type and tenancy systems of agricultural holdings. On the whole two sizes of holdings occur, large and small, with corresponding types of farming: plantations and peasant holdings. On some islands peasant holdings amount to only a small pro portion as for instance on the Leeward Islands and Barbados, on others their share of the agricultural land is considerable, as on the Windward Islands, Trinidad and Tobago. On the basis of a combination of several characteristics of land tenure five types of land property structure have ben distinguished and their distribution investigated in relation to economic and political situations. The aim of production is largely coincident regardless of size of holding. Accordingly the following economic regions can be distinguished: the economic region of monoculture (sugar cane, cocoa, coconut palms), the economic region of polyculture (tree plantations or arable) and the economic region of pastoralism. Each of these economic regions, which according to the aim of production forms a unit, is differentiated in the economic sub-regions of large and small holdings. Apart from the structure of the agricultural holdings, these two economic associations are distinguished from each other in a very pronounced way physiognomically, i. e. in the appearance of the economic landscape, and according to settlement structure. The spatial arrangement of these two economic associations within each economic region shows a clear dependence on physical conditions. The paper concludes with a discussion of the economic and social problems arising from this land property structure.